Long-term evolution coupled-fed loop antenna installed in the hinge slot region of a laptop computer. Issue 14 (22nd September 2018) - Nieh, Jo-Yen; Syu, Wei-Ming; Chen, Shu-Chuan; Wang, Ching-Cheng
Abstract: The present study proposed a long-term evolution (LTE) couple-feeding antenna design for laptop computers. The proposed antenna was installed in a closed hinge slot region. The loop structure of the antenna was designed to excite the closed hinge slot's resonance modes to extend operating bandwidth and antenna efficiency. Although the fabricated antenna measured only 25 mm × 4 mm, it was capable of covering the requirement for eight-band coverage to the LTE standard. Additionally, the antenna consisted of a feeding strip and a shorting strip, with which it was able to excite resonance modes in both its own loop's modes and the closed hinge slot's modes. Aside from a wide operating bandwidth, the minute antenna can also overcome the radiation efficiency problem caused by an all-metal environment. With antenna efficiency over 50% within the operating band, the design conforms to the actual needs of applications in laptop computers.